REALISASI SISTEM PENGENDALI LAMPU JARAK JAUH MENGGUNAKAN GSM SELULAR VIA SHORT MESSAGE SERVICES (SMS) - Sriyanto, Sriyanto; Nugroho, Bayu (Jurnal Informatika, 2007)
Computer ability to control the outside peripherals enable the computer can be made to become the more usefull equipments for its user. Through ports and expansion slots provided at computer, various digital equipments can be connected and controlled through computer. System that is realized in this research is a system of long distance controller of lamp by exploiting one of features from GSM Cellular, that is Short Message Services ( SMS) as information system having the character of real time, constructively computer as controller of Electronic switch which is connected to computer through PPI8255 Interface Â  This System Solution cover the realization from hardware in the form of GSM Cellular, RS232 Interface, PPI 8255 Interface and Electronic switch; software and Hardware. Software as controller device of hardware made using the Visual Basic V6.0 Programming Language. Software undertake to take the data of SMS at cellular phone memory, processing accepted data, storages data to conduct the arrangement to interface PPI8255Â  according to accepted information or data